Pelatihan Manajemen Pengelolaan Masjid Era Modern di Kecamatan Pangandaran: Mengokohkan Eksistensi dan Pelayanan Masjid: Modern Mosque Management Training in Pangandaran District: Strengthening the Existence and Service of Mosques - Abdullah, Mulyana; Fahrudin, Fahrudin; Faqihuddin, Achmad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Mosque management in the modern era demands extensive adaptation to long-established religious and community functions while introducing advanced technology integration to meet the continuously evolving needs and expectations of its congregation. This research focuses on the development and implementation of the training